2020
DOI: 10.3390/f11010104
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization and Expression Analysis of the Phosphate Starvation Response Gene, ClPHR1, from Chinese Fir

Abstract: The study on the function and sequence of PHR1 (Phosphate Starvation Response gene 1) gene, which plays a central role in plant phosphorus (Pi) signal regulatory network, is of great significance to further study response mechanisms to Pi deficiency. In this work, the previously selected Pi-efficient Chinese fir clone M32 was used as research material to obtain the full-length sequence of ClPHR1 transcription factors in Chinese fir by RACE (Rapid Amplification of cDNA Ends) full-length cloning technique, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…massoniana materials and Pi stress treatments were similar to previous research [36]. The plants were grown in perlite in an illuminated incubator with a cycle of 14 h/25 [40]. The phosphorus concentration in the treated nutrient solution was adjusted by KH 2 PO 4 .…”
Section: Plant Materials and Pi Stress Treatmentsmentioning
confidence: 99%
“…massoniana materials and Pi stress treatments were similar to previous research [36]. The plants were grown in perlite in an illuminated incubator with a cycle of 14 h/25 [40]. The phosphorus concentration in the treated nutrient solution was adjusted by KH 2 PO 4 .…”
Section: Plant Materials and Pi Stress Treatmentsmentioning
confidence: 99%
“…Strikingly, plants have evolved a range of morphological, physiological, and biochemical adaptation mechanisms (e.g., alteration of root architecture, interaction with symbiotic mycorrhizal fungi, secretion of organic acid anions, increased expression of phosphorus transporters, and changes in metabolic processes) to enhance the acquisition of Pi [4][5][6]. Because of soil phosphorus enrichment and water pollution caused by traditional fertilization methods, as well as the non-renewable nature of phosphorus resources, it has become one of the hot spots of global research to study the mechanism of high-efficiency absorption Pi of plants to excavate the genotype of high-efficiency Pi utilization [4][5][6][7][8][9]. Numerous studies on crops and trees, such as Zea mays (maize) [10], Lycopersicon esculentum (tomato) [11], Camellia oleifera [12], and Pinus massoniana [13], have shown that there are significant genotypic differences in the uptake, transport, and utilization efficiency of soil phosphorus among different species or different varieties of the same species.…”
Section: Introductionmentioning
confidence: 99%
“…(Chinese fir) is one of the most important commercial timber and afforestation species in southern China [14]. However, the low level of active Pi in the acidic soil of southern forest lands and continuous replanting on the same sites are important factors to restrict the long-term productivity of Chinese fir plantations [9]. Previous studies have shown that Pi-deficiency stress had a significant influence on biomass accumulation and distribution pattern, root system architecture, acid phosphatase activity, endogenous hormone content, and protein expression in Chinese fir [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%